Pengembangan Penuntun Praktikum Uji Zat Makanan pada Susu Kambing di Kelas XI Sekolah Menengah Atas - Al-Islami, Ilma; Tenriawaru, Andi Besse; Candramila, Wolly (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Practical guide books need to be prepared to ensure a good practicum activity. The sample used in the practicum should also be chosen carefully so as not to lead to misconception in students. This study aims to develop and test the feasibility of a practical guide for testing nutrients in goat’s milk in Food Substances for class XI SMA. This type of research is research and development (R&D) that uses the first 3 stages of the 4D model (define, design, develop, and disseminate). The research instrument used was a validation sheet in the form of a questionnaire. There are 5 product validators consisting of 2 lecturers from the Biology Education Study Program, FKIP Tanjungpura University and 3 biology teachers from 3 high schools in Pontianak City. The type of validation used is content validity which contains 3 aspects, namely aspects of format, content, and language. The results showed that the development of a practicum guide for testing nutrients in goat’s milk was successfully carried out and obtained a validity value of CVR=1. Thus, the practicum guide is valid in content and deserves to be tested both on a limited and broad basis to ensure the suitability of the development design with the needsâ€™ analysis. The practical guide for testing nutrients in goat’s milk is also expected to be able to provide solutions to the misconceptions found in the Food Substances related to the selection of more effective and efficient practicum materials.